Cover Feature: Phospholenes from Phosphabenzenes by Selective Ring Contraction (Chem. Eur. J. 72/2022). Issue 72 (14th December 2022) - Lin, Jinxiong; Coles, Nathan T.; Dettling, Lea; Steiner, Luca; Felix Witte, J.; Paulus, Beate; Müller, Christian
Abstract : A six‐membered phosphabenzene contracts to a five‐membered hydroxylphospholene oxide in the presence of hydrochloric acid. This unusual reaction can only proceed because the special electronic properties of phosphinines, in combination with the particular reactivity of low‐coordinate organophosphorus species, allow sequential reactions at the aromatic phosphorus heterocycles; this is in clear contrast to functionalized pyridines. More information can be found in the Research Article by C. Müller and co‐workers (DOI: 10.1002/chem.202203406 ).